GLOBAL ANALYSIS IN THE NUMERICAL TREATMENT OF THE SKYRME EQUATION - Ái Việt, Nguyễn (Vietnam Journal of Science and Technology, 2014)
The Skyrme equation used widely in Physics is singular at the boundary r = 0. The singularity causes uncontrollable instabilities in the numerical solutions. This paper presents a new computa- tional schema to overcome this difficulty to give the solutions with an arbitrarily high accuracy by combining the numerical methods with a global analysis. PACS numbers: 21.65.-f,11.30.Rd, 02.60.Lj,13.75.Gx, 13.85.-t Keywords: Computational Physics, Numerical Computation, Differential Equation.